KOMUNIKASI PENGURANGAN KETIDAKPASTIAN PEMBINA GOLONGAN PENEGAK DALAM PENDIDIKAN KEPRAMUKAAN DI SMA PASUNDAN 8 BANDUNG (KOMUNIKA BANGSA, 2023)
AbstrakThis research is entitled Communication of Uncertainty Reduction of Scout Leaders in Scouting Education at Pasundan 8 Bandung High School. The purpose of this study is to describe the communication carried out by scout coaches towards the implementation of scouting education in order to know the character and character of students in the perspective of uncertainty reduction at Pasundan 8 Bandung High School. This type of research is descriptive qualitative with a research approach to the study of uncertainty reduction in interpersonal communication. The data source of this research is divided into two types of data sources, primary data obtained from informants namely scout coaches, instructors, and scout members of class X to class XII. Furthermore, the data collection techniques used are direct observation, interviews and documentation, participation. Then, the data analysis technique uses three stages, namely data reduction, data presentation and conclusion drawing. The results of this study indicate the application of coach communication in scouting education. Primary communication flow is the main one applied in conducting interactions and secondary seeks to be minimized even in sudden situations. Uncertainty reduction methods tend to be passive and interactive strategies. The implication of this research, encourages especially the coach as the person in charge to pay attention to the implementation of the scouting education system can run as expected so that it is still possible to be developed and completed by analyzing other parts of Scouting to become a better and more effective Scouting Education. Keywords: Scouting Education, Communication, Uncertainty Reduction